Restoring function and quality of life through early interim obturator therapy after left hemimaxillectomy - Astila Fitriana; Agus Dahlan; Riddo A. Rudhanton (Indonesian Journal of Prosthodontic, 2025)
Background: Maxillectomy, whether total or partial, results in significant anatomical and functional disturbances, including oronasal communication, impaired mastication, speech difficulty, and esthetic disfigurement. These sequelae can severely affect a patient’s nutritional status, social interaction, and psychological well‑being. Rehabilitation following maxillectomy aims to restore oral function and improve quality of life through obturator prostheses that close the surgical defect Objective: This case report aims to present the clinical management for hemi-maxillectomy Case Report : This report presents the case of a 76-year-old female, a housewife, who was referred to the Prosthodontic Clinic of RSKGMP Universitas Airlangga by an Oncology Surgeon for the fabrication of an obturator. The patient presented two weeks after hemi-maxillectomy surgery performed on. The patient complained of oronasal communication, hyper nasal speech, and difficulties in mastication and swallowing postoperatively; she had no previous experience using any obturator prosthesis. An interim acrylic obturator was planned to restore oral-nasal separation, improve speech intelligibility and swallowing function, and support psychological adaptation during the healing phase. Clinical procedures included impression-taking of the maxillary defect, jaw relation recording, tooth arrangement, and fabrication of an acrylic obturator supported by the remaining teeth. Follow-up evaluations demonstrated marked improvement in speech resonance, masticatory efficiency, deglutition, and patient comfort, with gradual adaptation to the prosthesis. Conclusion: This case report highlights the importance of timely interim obturator rehabilitation in elderly post-hemi‑maxillectomy patients to restore function, improve quality of life, and reduce psychological distress. Keyword maxillofacial prosthesis, obturator, maxillectomy, spindle cell sarcoma